Integrated Analysis of Microbiome and Transcriptome Data Reveals the Interplay Between Commensal Bacteria and Fibrin Degradation in Endometrial Cancer - Li, Chao; Gu, Ye; He, Qizhi; Huang, Jian; Song, Yunfeng; Wan, Xiaoping; Li, Yiran (Frontiers in Cellular and Infection Microbiology, 2021)
The gut-uterus axis plays a pivotal role in the pathogenesis of endometrial cancer (EC). However, the correlations between the endometrial microbiome and endometrial tumor transcriptome in patients with EC and the impact of the endometrial microbiota on hematological indicators have not been thoroughly clarified. In this prospective study, endometrial tissue samples collected from EC patients (n = 30) and healthy volunteers (n = 10) were subjected to 16S rRNA sequencing of the microbiome. The 30 paired tumor and adjacent nontumor endometrial tissues from the EC group were subjected to RNAseq. We found that Pelomonas and Prevotella were enriched in the EC group with a high tumor burden. By integrating the microbiome and hematological indicators, a correlation was observed between Prevotella and elevated serum D-dimer (DD) and fibrin degradation products (FDPs). Further transcriptome analysis identified 8 robust associations between Prevotella and fibrin degradation-related genes expressed within ECs. Finally, the microbial marker of Prevotella along with DD and FDPs showed a high potential to predict the onset of EC (AUC = 0.86). Our results suggest that the increasing abundance of Prevotella in endometrial tissue combined with high serum DD and FDP contents may be important factors associated with tumor burden. The microbe-associated transcripts of host tumors can partly explain how Prevotella promotes DD and FDPs.